DEVELOPING THE ENGLISH STUDENTSâ VERBAL SKILLS IN ISLAMIC STUDIES IAIN SULTAN AMAI GORONTALO - Aba, La (JURUSAN MANAJEMEN PENDIDIKAN ISLAM, 2014)
To develop the English studentsâ verbal skill is need understood the studentsâ lack before. The studentsâ lack like; lack of vocabulary, lack of grammatically and the lack of selfconfidence. Developing verbal skillÂ is not depend on the studentsâ ability in recognizing vocabulary and understanding grammar but also depend on the teachersâ motivationÂ and teaching strategy.